2014
DOI: 10.1074/jbc.m114.561563
|View full text |Cite
|
Sign up to set email alerts
|

Error-prone Replication Bypass of the Primary Aflatoxin B1 DNA Adduct, AFB1-N7-Gua

Abstract: Background: Aflatoxin B 1 exposure causes mutations that are associated with liver cancer. Results: The AFB 1 -N7-Gua adduct is highly mutagenic in primate cells, with contributions by both replicative and translesion synthesis DNA polymerases. Conclusion: AFB 1 -N7-Gua adduct is a biologically relevant DNA adduct. Significance: This is the first study demonstrating the mutagenicity of AFB 1 -N7-Gua in mammalian cells and the identification of candidate DNA polymerases involved in these processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 35 publications
1
49
0
Order By: Relevance
“…Based on both our previous biochemical data that demonstrated the ability of pol ζ to replicate past AFB 1 -induced DNA adducts (15,17) and the enhanced cytotoxicity in Rev3L-deficient cells described above, we hypothesized that one possible role of pol ζ in tolerance to AFB 1 exposure could be bypass of DNA lesions. In this case, the replication efficiency of single-stranded vectors containing an AFB 1 -Fapy-dG adduct would be decreased in cells in which the level of pol ζ was transiently knocked down.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on both our previous biochemical data that demonstrated the ability of pol ζ to replicate past AFB 1 -induced DNA adducts (15,17) and the enhanced cytotoxicity in Rev3L-deficient cells described above, we hypothesized that one possible role of pol ζ in tolerance to AFB 1 exposure could be bypass of DNA lesions. In this case, the replication efficiency of single-stranded vectors containing an AFB 1 -Fapy-dG adduct would be decreased in cells in which the level of pol ζ was transiently knocked down.…”
Section: Resultsmentioning
confidence: 99%
“…These data revealed that yeast pol ζ was exceptional in its ability to replicate past the AFB 1 -Fapy-dG adduct, but the bypass was highly mutagenic: pol ζ preferentially incorporated an A opposite the lesion and extended the primer strand beyond the mismatch (15). In contrast, AFB 1 -N7-dG was bypassed by pol ζ in an error-free manner (17). To facilitate the analysis of a role for pol ζ in cellular tolerance to AFB 1 -induced DNA damage in vivo, an experimental strategy has been designed using isogenic pol ζ proficient, deficient, and complemented mouse embryo fibroblasts (MEFs).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The G:C→T:A dominance in the spectra was expected due to the mutational properties of individual AFB 1 -DNA adducts (all of which occur at guanines) (12,13,29,30), the mutational spectra in vitro and in vivo of AFB 1 in cells and tissues (12)(13)(14)(15)(16)(17)(18), and observed patterns of mutations in human tumors (27,28). Unexpected, however, was the high G→T mutation yield at selected guanyl residues in the 16 possible three-base contexts (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…cells, the AFB 1 -Fapy-dG adduct is more mutagenic than AFB 1 -N7-dG with mutation frequencies measured at 97% and 32%, respectively; the mutagenic spectrum for each was dominated by G-to-T transversions (13)(14)(15). Between the two anomers of AFB 1 -Fapy-dG, the α species was a severe block to replication, whereas the β species was implicated as a major contributor to mutagenesis (15).…”
Section: Significancementioning
confidence: 99%